(untitled) - Brower, Robert H. (Stanford, CA., 1961)
It is a critical study rather than an anthology, but it contains many poems [some 300], all translated with unmistakable care ... As Brower and Miner have demonstrated in this epoch making book, the achievement of Japanese court poetry within its deliberately restricted domain is impressive. It deserves this long-awaited attention.
Keywords: Japanese poetry; History and criticism